The Factors Contributing toward the Effectiveness of Afterschool Program Management in Taiwan - Enricho Fiktorando Purba; Sheng Yao Cheng; Nasib Tua Lumban Gaol (Universitas Kristen Satya Wacana, 2021)
The paper reports the result of an investigation on the effectiveness of afterschool program management in Taiwan that was conducted in the Yonglin Hope School through an in-depth investigation consisting of observations, interviews and questionnaire. The involved participants were the director of Institute for Disadvantaged Students’ Learning (IDSL), Yonglin Foundation, school principal, social workers, and tutors. This study found five main factors that contribute toward the effectiveness of afterschool program management in Yonglin Hope School, namely setting specific goals, having professional development and training, continuous evaluation, class sizes and designed curriculum. In addition, the effectiveness of the afterschool program was supported by five main activities (i.e., remedial teaching, homework assistance, English summer camp, special event and field trips) to improve the students’ knowledge and experience. Furthermore, it was also supported by an integrated and interconnected role of different stakeholders (i.e., Yonglin Foundation, Institute for Disadvantaged Students’ Learning, school principals, social workers and tutors) who played an important role to make this program being success. Importantly, tutors as the main actor played the most important role to improve students’ achievements.